Find the length of the chord of the ellipse \[\dfrac{{{x^2}}}{{25}} + \dfrac{{{y^2}}}{{16}} = 1\], whose middle point is \[\left( {\dfrac{1}{2},\dfrac{2}{5}} \right)\].
Answer
Verified
480.9k+ views
Hint: To solve the question first, we have to find out the equation of the chord. The intersection points of the chord and ellipse can be found out by solving the equations of the chord and ellipse. Finally, by using the distance formula we get the distance between two intersection points that is the length of the chord.
Complete step-by-step solution:
We know that the general equation of an ellipse with semi major axis ’a’ and semi minor axis ‘b’ is given by
\[\dfrac{{{x^2}}}{{{a^2}}} + \dfrac{{{y^2}}}{{{b^2}}} = 1\] ………………….. (1)
From the question the equation of the ellipse is given by
\[ \dfrac{{{x^2}}}{{25}} + \dfrac{{{y^2}}}{{16}} = 1 \\
\Rightarrow \dfrac{{{x^2}}}{{{5^2}}} + \dfrac{{{y^2}}}{{{4^2}}} = 1 \\ \] ……………………………… (2)
We know the formula that the equation of the chord of an ellipse \[\dfrac{{{x^2}}}{{{a^2}}} + \dfrac{{{y^2}}}{{{b^2}}} = 1\] having midpoint is \[\left( {{x_{1,}}{y_1}} \right)\]given by
\[\dfrac{{x{x_1}}}{{{a^2}}} + \dfrac{{y{y_1}}}{{{b^2}}} - 1 = \dfrac{{{x^2}}}{{{a^2}}} + \dfrac{{{y^2}}}{{{b^2}}} - 1\] ………………………………….. (3)
Applying this formula, the equation of the chord of \[\dfrac{{{x^2}}}{{25}} + \dfrac{{{y^2}}}{{16}} = 1\]having mid point \[\left( {\dfrac{1}{2},\dfrac{2}{5}} \right)\] is given by
\[ \dfrac{{x \times \dfrac{1}{2}}}{{{5^2}}} + \dfrac{{y \times \dfrac{2}{5}}}{{{4^2}}} - 1 = \dfrac{{{{\left( {\dfrac{1}{2}} \right)}^2}}}{{{5^2}}} + \dfrac{{{{\left( {\dfrac{2}{5}} \right)}^2}}}{{{4^2}}} - 1 \\
\Rightarrow \dfrac{x}{{50}} + \dfrac{y}{{40}} = \dfrac{1}{{100}} + \dfrac{1}{{100}} \\
\Rightarrow 4x + 5y = 4 \\ \] ………………………………. (4)
From eq. (4) we can deduce
\[y = 4\left( {\dfrac{{1 - x}}{5}} \right)\] ……………………………………. (5)
\[ \Rightarrow \dfrac{{{x^2}}}{{25}} + \dfrac{{{{\left\{ {4\left( {\dfrac{{1 - x}}{5}} \right)} \right\}}^2}}}{{16}} = 1 \\
\Rightarrow \dfrac{{{x^2}}}{{25}} + \dfrac{{{{(1 - x)}^2}}}{{25}} = 1 \\
\Rightarrow 2{x^2} - 2x - 24 = 0 \\
\Rightarrow {x^2} - x - 12 = 0 \\
\Rightarrow {x^2} - 4x + 3x - 24 = 0 \\
\Rightarrow x(x - 4) + 3(x - 4) = 0 \\
\Rightarrow (x - 4)(x + 3) = 0 \\
\Rightarrow x = 4 or - 3 \\ \] …………………………………… (6)
Substituting the value of x in Eq. (5) we get the values of y.
For\[x = 4\], \[y = 4\left( {\dfrac{{1 - 4}}{5}} \right) = - \dfrac{{12}}{5}\]
And for \[x = - 3\], \[y = 4\left( {\dfrac{{1 + 3}}{5}} \right) = \dfrac{{16}}{5}\]
Therefore, the intersection points are \[\left( {4, - \dfrac{{12}}{5}} \right)\] and \[\left( { - 3,\dfrac{{16}}{5}} \right)\]. Those are the coordinates of the end points of the chord.
We know the distance between the points joining \[({x_1},{y_1})\] and \[({x_2},{y_2})\]is given by
\[d = \sqrt {{{({x_2} - {x_1})}^2} - {{({y_2} - {y_1})}^2}} \] ……………………… (7)
Hence applying this formula, we get the distance between the intersection points \[\left( {4, - \dfrac{{12}}{5}} \right)\] and \[\left( { - 3,\dfrac{{16}}{5}} \right)\] that is the length of the chord which is given by
\[ d = \sqrt {{{( - 3 - 4)}^2} - {{\left( {\dfrac{{16}}{5} + \dfrac{{12}}{5}} \right)}^2}} \\
= \dfrac{7}{5}\sqrt {41} \\ \]
Hence we got the length of the chord = \[\dfrac{7}{5}\sqrt {41} \].
Note: While solving the equations of the chord and the ellipse we must get two coordinates since the degree of the equation of the ellipse is 2 and the obtained coordinates are the intersecting points. In an alternative method, to find the point of intersection of the chord and ellipse we can solve the equations for y and setting the expressions for y equal to each other we get values of x.
Complete step-by-step solution:
We know that the general equation of an ellipse with semi major axis ’a’ and semi minor axis ‘b’ is given by
\[\dfrac{{{x^2}}}{{{a^2}}} + \dfrac{{{y^2}}}{{{b^2}}} = 1\] ………………….. (1)
From the question the equation of the ellipse is given by
\[ \dfrac{{{x^2}}}{{25}} + \dfrac{{{y^2}}}{{16}} = 1 \\
\Rightarrow \dfrac{{{x^2}}}{{{5^2}}} + \dfrac{{{y^2}}}{{{4^2}}} = 1 \\ \] ……………………………… (2)
We know the formula that the equation of the chord of an ellipse \[\dfrac{{{x^2}}}{{{a^2}}} + \dfrac{{{y^2}}}{{{b^2}}} = 1\] having midpoint is \[\left( {{x_{1,}}{y_1}} \right)\]given by
\[\dfrac{{x{x_1}}}{{{a^2}}} + \dfrac{{y{y_1}}}{{{b^2}}} - 1 = \dfrac{{{x^2}}}{{{a^2}}} + \dfrac{{{y^2}}}{{{b^2}}} - 1\] ………………………………….. (3)
Applying this formula, the equation of the chord of \[\dfrac{{{x^2}}}{{25}} + \dfrac{{{y^2}}}{{16}} = 1\]having mid point \[\left( {\dfrac{1}{2},\dfrac{2}{5}} \right)\] is given by
\[ \dfrac{{x \times \dfrac{1}{2}}}{{{5^2}}} + \dfrac{{y \times \dfrac{2}{5}}}{{{4^2}}} - 1 = \dfrac{{{{\left( {\dfrac{1}{2}} \right)}^2}}}{{{5^2}}} + \dfrac{{{{\left( {\dfrac{2}{5}} \right)}^2}}}{{{4^2}}} - 1 \\
\Rightarrow \dfrac{x}{{50}} + \dfrac{y}{{40}} = \dfrac{1}{{100}} + \dfrac{1}{{100}} \\
\Rightarrow 4x + 5y = 4 \\ \] ………………………………. (4)
From eq. (4) we can deduce
\[y = 4\left( {\dfrac{{1 - x}}{5}} \right)\] ……………………………………. (5)
\[ \Rightarrow \dfrac{{{x^2}}}{{25}} + \dfrac{{{{\left\{ {4\left( {\dfrac{{1 - x}}{5}} \right)} \right\}}^2}}}{{16}} = 1 \\
\Rightarrow \dfrac{{{x^2}}}{{25}} + \dfrac{{{{(1 - x)}^2}}}{{25}} = 1 \\
\Rightarrow 2{x^2} - 2x - 24 = 0 \\
\Rightarrow {x^2} - x - 12 = 0 \\
\Rightarrow {x^2} - 4x + 3x - 24 = 0 \\
\Rightarrow x(x - 4) + 3(x - 4) = 0 \\
\Rightarrow (x - 4)(x + 3) = 0 \\
\Rightarrow x = 4 or - 3 \\ \] …………………………………… (6)
Substituting the value of x in Eq. (5) we get the values of y.
For\[x = 4\], \[y = 4\left( {\dfrac{{1 - 4}}{5}} \right) = - \dfrac{{12}}{5}\]
And for \[x = - 3\], \[y = 4\left( {\dfrac{{1 + 3}}{5}} \right) = \dfrac{{16}}{5}\]
Therefore, the intersection points are \[\left( {4, - \dfrac{{12}}{5}} \right)\] and \[\left( { - 3,\dfrac{{16}}{5}} \right)\]. Those are the coordinates of the end points of the chord.
We know the distance between the points joining \[({x_1},{y_1})\] and \[({x_2},{y_2})\]is given by
\[d = \sqrt {{{({x_2} - {x_1})}^2} - {{({y_2} - {y_1})}^2}} \] ……………………… (7)
Hence applying this formula, we get the distance between the intersection points \[\left( {4, - \dfrac{{12}}{5}} \right)\] and \[\left( { - 3,\dfrac{{16}}{5}} \right)\] that is the length of the chord which is given by
\[ d = \sqrt {{{( - 3 - 4)}^2} - {{\left( {\dfrac{{16}}{5} + \dfrac{{12}}{5}} \right)}^2}} \\
= \dfrac{7}{5}\sqrt {41} \\ \]
Hence we got the length of the chord = \[\dfrac{7}{5}\sqrt {41} \].
Note: While solving the equations of the chord and the ellipse we must get two coordinates since the degree of the equation of the ellipse is 2 and the obtained coordinates are the intersecting points. In an alternative method, to find the point of intersection of the chord and ellipse we can solve the equations for y and setting the expressions for y equal to each other we get values of x.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE